Locating Specific Acupoints Large Intestine 4 (LI4) and Large Intestine 6 (LI6) in Cadavers Using Anthropometric and Cun Measurement Systems - Gregory P. Casey (Medical Association of Pharmacopuncture Institute, 2020)
Background: Anthropometric and anatomical Chinese inch measurement (CUN) systems are useful in understanding the location of acupoints; however, locating acupoints is challenging. Objectives: The study aimed to locate LI4 and LI6, to measure differences and similarities in body dimensions based on sex using anthropometric and CUN systems, and to observe the relationship between f-cun and b-cun. Methods: 25 forearms and hands from 16 embalmed cadavers had body dimensions measured using anthropometric and CUN systems. LI4 and LI6 were located using a combination of both systems. Data were compiled and calculated to observe any variation in means and ranges. Statistical analysis was performed using a paired t-test. Results: LI4 was found on the skin at the lateral border of the midpoint of the second metacarpal bone. LI6 was found 3 cun or 74 ± 8 mm from LI5. Differences were observed between male and female cadavers and a large difference between f-cun and b-cun measurements of 1.5 to 3 cun. There were positive correlations between several body dimensions observed. Conclusions: LI4 was located on the dorsum of the hand, radial to the midpoint of the second metacarpal bone. LI6 was located 3 cun from LI5 with an error of 1 to ½ cun variation. The differences in f-cun and b-cun in isolating LI6 seem to account for this error. Future studies using cadavers may need to take this error into consideration for variation and measuring differences.